Role of Homoeopathic Genus Epidemicus in Epidemic and Pandemic Outbreaks – A Review on Historical Perspective (Advancements in Homeopathic Research, 2022)
Homoeopathic medications have been used as a method of preventive immunotherapy for over 200 years.Vaccines are considered as an answer to epidemic outbreaks. But at the same time, it shall be recognized that different mode of treatments can also play significant role in managing the epidemics, which could be safer alternatives. Genus Epidemicus, a method used in homoeopathy for preventing the spread of diseases in various disease outbreaks such as chikungunya, dengue fever, Japanese encephalitis and cholera, stands the test of time.This method in homoeopathy for infectious disease-specific immunization is known as homeoprophylaxis.It has been utilized for the management of both epidemic and endemic contagious diseases.Dr Hahnemann suggested that whenever there is an epidemic, it shall be considered as a new and unique and a perfect disease picture can be deducted from seeing several such cases. Based on this he suggests forming a totality and finds the suitable homeopathic remedy.Homeopathy has played a significant role in various epidemics so far.It is the time for integrated approach where different therapies bring in their best for patients benefit and to work at a same platform hand in hand for human betterment.
Keywords: Homoeopathy; Epidemics; Pandemics; Homeoprophylaxis; Hahnemann; Genus epidemicus